De la ville pionnière à la cité - Vaguet, Yvette (Belgeo, 2019)
Hydrocarbons continue to structure the geography and geopolitics of the world. Nevertheless, places of extraction sometimes at the limit of the ecumene, and the lifestyles of their residents draw little attention. The plain of the Ob river is an example in the Arctic and subarctic zone. The oil and gas towns there are at the frontier, they remain at the limit of viability in a market economy. They experience undergoing transformations since the fall of the USSR. They opened up to the competition whereas they had few assets for residents, and suffered from the withdrawal of the State.The phenomenological approach allows to account for and discuss the material realities of the mutations of these post-Soviet urban landscapes. The image and the text combine to highlight changes as a result mainly of the introduction of the market economy, and that respond to the aspirations of residents. Some local forms of normalization are observed there, a result of the globalization declined locally. The frontier town becomes a modern city. Les hydrocarbures continuent de structurer la géographie et la géopolitique de notre monde. Néanmoins, les lieux d’extraction parfois à la limite de l’œcoumène et les modes de vie des résidents retiennent, somme toute, fort peu l’attention. La plaine de l’Ob en constitue un excellent observatoire, dans la zone arctique et subarctique. Les villes pionnières pétrolières et gazières, toujours à la limite de la viabilité dans une économie désormais de marché, y enregistrent des transformations profondes depuis la chute de l’URSS. Tandis qu’elles avaient peu d’atouts pour les résidents et souffraient du désengagement de l’Etat, elles se sont ouvertes à la concurrence. En adoptant une approche phénoménologique, il est possible de rendre compte et discuter des réalités matérielles des mutations de ces paysages urbains post-soviétiques. L’image et le texte se combinent pour mettre en évidence les changements opérés largement en raison de l’introduction de l’économie de marché et qui répondent aux ...